An overview of hypertension and cardiac involvement in Asia: Focus on heart failure. Issue 3 (19th January 2020) - Soenarta, Arieska Ann; Buranakitjaroen, Peera; Chia, Yook‐Chin; Chen, Chen‐Huan; Nailes, Jennifer; Hoshide, Satoshi; Minh, Huynh Van; Park, Sungha; Shin, Jinho; Siddique, Saulat; Sison, Jorge; Sogunuru, Guru Prasad; et al.
Abstract: Cardiovascular Disease (CVD) is the leading cause of deaths worldwide, contributing to about 30% of all deaths. Half of the cases of CVD are estimated in Asia, the world's most populous continent. Hypertension, a major modifiable risk factor for CVD, results in more deaths than any other CV risk factors in the Asian regions. The total number of patients with hypertension is likely to grow as the population ages. The proportion of the elderly population aged 65 years or more in Asia is expected to increase from 7.4% in 2015 to 10.9% in 2030. It is important to note that more than half (54%) of the world's population live in Asia. Aside of being the biggest single risk factor for global deaths, hypertension is also an important precursor and most common risk factor of heart failure (HF). An increase in HF prevalence is clearly related to the rapid epidemiological transition caused by changes in lifestyle in Asian countries. However, the availability of data on HF burden and health care delivery is limited in Asia compared with Europe and North America. This reality has driven the working group of Asian experts for example the HOPE Asia Network to concentrate on hypertension as risk factors for CVD, with the mission to improve the management of hypertension resulting in organ protection toward a goal of achieving "ZERO" CV event in Asia. This paper aims to give an overview regarding the heart problems caused by hypertension in Asia, focus on HF.